Study and Simulation of an Edge Couple Split Ring Resonator (EC-SRR) on Truncated Pyramidal Microwave Absorber - Nornikman, H; Ahmad, B. H.; Othman, A. R; Abdul Aziz, M. Z. A; Malek, F; Imran, H (The Electromagnetics Academy, 2012)
Split ring resonator (SRR) structure can potentially be incorporated onto the truncated pyramidal microwave absorber. This study considers three different patterns of edge couple split ring resonator (EC-SRR) designs. Each EC-SRR design is then placed onto the truncated pyramidal microwave absorber. Outer split gap dimension widths of the EC-SRR are varied, and the various S21 performances are compared. This EC-SRR truncated pyramidal microwave absorber is simulated using CST Microwave Studio simulation software. The study and simulation are performed in low frequency range (0.01 GHz to 1 GHz) as well as in microwave frequencies range (1 GHz to 20 GHz). Simulation results of this EC-SRR show improvement of reflection loss and S11 performance in the high frequency range of the pyramidal truncated microwave absorber.